Energy-efficient user association and cell sleeping strategy for multi-tier ultra-dense small cell networks - Sun, Yang; Chang, Yongyu (Electronics letters, 2018)
In this letter, the authors formulate the energy-efficient user association and cell sleeping optimisation problem which applies to the multi-tier ultradense network scenarios as a complex 0–1 integer programming and propose an alternating iterative method to solve the problem via two low-complexity sub-problems. The simulation results show that the proposed strategy can steadily reduce overall energy consumption compared with the existing strategies.